Identification and Characterization of a Transcribed Distal Enhancer Involved in Cardiac Kcnh2 Regulation - Malou van den Boogaard; Jan Hendrik van Weerd; Amira C. Bawazeer; Ingeborg B. Hooijkaas; Harmen J.G. van de Werken; Federico Tessadori; Wouter de Laat; Phil Barnett; Jeroen Bakkers; Vincent M. Christoffels (Cell Reports, 2019)
Summary: The human ether-a-go-go-related gene KCNH2 encodes the voltage-gated potassium channel underlying IKr, a current critical for the repolarization phase of the cardiac action potential. Mutations in KCNH2 that cause a reduction of the repolarizing current can result in cardiac arrhythmias associated with long-QT syndrome. Here, we investigate the regulation of KCNH2 and identify multiple active enhancers. A transcribed enhancer ∼85 kbp downstream of Kcnh2 physically contacts the promoters of two Kcnh2 isoforms in a cardiac-specific manner in vivo. Knockdown of its ncRNA transcript results in reduced expression of Kcnh2b and two neighboring mRNAs, Nos3 and Abcb8, in vitro. Genomic deletion of the enhancer, including the ncRNA transcription start site, from the mouse genome causes a modest downregulation of both Kcnh2a and Kcnh2b in the ventricles. These findings establish that the regulation of Kcnh2a and Kcnh2b is governed by a complex regulatory landscape that involves multiple partially redundantly acting enhancers. : KCNH2 encodes a potassium channel critical for cardiac repolarization. Van den Boogaard et al. identified a transcribed cardiac-specific enhancer physically contacting Kcnh2. Genomic deletion by CRISPR/Cas9 caused a modest decrease in ventricular Kcnh2a and Kcnh2b expression, demonstrating the complexity of the regulatory landscape regulating Kcnh2 expression. Keywords: Kcnh2, hERG, LQTS, enhancer, transcriptional regulation, regulatory element, CRISPR genome editing, chromatin conformation, ncRNA